High-voltage-resistant deep eutectic-based in-situ polymerization solid electrolyte as well as preparation and application thereof

The organic framework formed by in-situ polymerization of deep eutectic solution and monomers solves the contradictory problems of mechanical properties and conductivity of polymer electrolytes in high-energy density lithium-ion batteries, and realizes a solid electrolyte with high voltage and high electrochemical stability, which is suitable for high voltage systems.

CN119742439APending Publication Date: 2025-04-01INSTITUTE OF PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 6 Cited by

Patent Information

Application Number
CN202411916559.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

When used in high-energy-density lithium-ion batteries, it is difficult to take into account high ion conductivity and mechanical properties, and is not resistant to high voltage and has poor thermal stability, resulting in limited application in high voltage systems.

Method used

By in situ polymerizing the deep eutectic solution, additives and monomers in situ, a deep eutectic based in situ polymerization solid electrolyte that withstands high voltage is formed. The electrolyte forms an organic framework through the synergy of a strongly interacting deep eutectic solution and specific additives, which improves the mechanical strength and electrochemical stability of the electrolyte.

Benefits of technology

It realizes a solid electrolyte with wide electrochemical window, high ionic conductivity, high mechanical strength, good flame retardancy and wide temperature applicability. It is suitable for high voltage systems above 4.6V, solving the solid-solid contact problem at the solid-state battery interface and the side reaction between the electrolyte and the lithium metal negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742439A_ABST
    Figure CN119742439A_ABST
Patent Text Reader

Abstract

The invention relates to a high-voltage-resistant deep eutectic-based in-situ polymerization solid electrolyte as well as preparation and application thereof. The in-situ polymerization solid electrolyte is obtained through an in-situ polymerization reaction of a precursor solution comprising 30-80 wt% of a deep eutectic solution, 10-50 wt% of a polymerizable monomer, 1-30 wt% of an additive and 0.05-10 wt% of an initiator; the deep eutectic solution comprises a lithium salt and a hydrogen bond donor organic solvent; the hydrogen bond donor organic solvent comprises a nitrile solvent and a non-nitrile solvent; the polymerizable monomer comprises a monomer for free radical-initiated polymerization or ring-opening polymerization; the additive comprises lithium nitrate and fluoroethylene carbonate. The high-voltage-resistant in-situ polymerization solid electrolyte formed by in-situ compounding of an organic framework formed by in-situ polymerization of a deep eutectic solution, an additive and a monomer has the excellent characteristics of wide electrochemical window, high ionic conductivity, high mechanical strength, good flame retardance, wide-temperature applicability and the like, and can be suitable for a high-voltage system of 4.6 V or above; the solid-solid contact problem of a solid-state battery interface is effectively solved, and the side reaction between the electrolyte and the lithium metal negative electrode is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte and a preparation method and application thereof. Background Art

[0002] In recent years, due to the rapid development of portable electronic devices, electric vehicles and smart grids, lithium-ion batteries have received widespread attention in order to meet the growing demand for energy storage and other fields. At present, the energy density of liquid lithium-ion batteries has approached the theoretical limit, and as the energy density increases, the battery system will become more unstable.

[0003] Electrolytes can be divided into two categories according to their physical state: liquid electrolytes and solid electrolytes. Liquid electrolytes are widely used in lithium-ion batteries due to their high ionic conductivity. However, liquid electrolytes are volatile, flammable and leaky, which hinders their application in lithium batteries. Solid electrolytes are divided into two categories: inorganic solid electrolytes and polymer electrolytes. Compared with inorganic solid electrolytes, polymer electrolytes have the advantages of excellent processability, interfacial compatibility and low cost, and are considered to be an effective strategy to solve the safety problems of lithium-ion batteries. However, the poor lithium ion conductivity, high voltage resistance and poor thermal stability of polymer electrolytes limit their further application in high energy density lithium-ion batteries.

[0004] The prior art prepares a polymer electrolyte that is a physical gel polymer by adding a certain amount of liquid plasticizer or solvent into the polymer-salt system, and forms a cross-linked network through physical interactions such as crystallization, hydrogen bond interaction, and ionic interaction. In order to obtain higher ionic conductivity, the existing polymer electrolyte needs to increase the solvent content, but high solvent content will lead to reduced mechanical properties of the gel polymer, and flammable solvents also have the risk of thermal runaway of the battery. Although reducing the solvent content can improve the mechanical strength, the ionic conductivity is reduced, which seriously affects the performance of the battery. In addition, polymer electrolysis also faces the problem of narrow electrochemical window. Therefore, how to solve the contradiction between ionic conductivity and mechanical strength of solid polymer electrolytes and how to solve the adaptation problem of polymer electrolyte oxidation window and high voltage positive electrode are related to whether solid-state batteries can be widely used in industry, and they need to be solved urgently.

[0005] In summary, the practical application of polymer electrolytes still faces problems such as difficulty in balancing ionic conductivity and mechanical properties, poor thermal safety, poor contact interface chemistry and electrochemical stability, and difficulty in matching with high-voltage positive electrode materials, which limits their application in high-energy density batteries. Summary of the invention

[0006] The purpose of the present invention is to provide a high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte and its preparation and application in view of the defects in the prior art. By in-situ compounding the organic framework formed by in-situ polymerization of the deep eutectic solution, additives and monomers to form a high-voltage resistant in-situ polymerized solid electrolyte, the solid-solid contact problem at the interface of the solid-state battery can be effectively solved and the side reaction between the electrolyte and the lithium metal negative electrode can be reduced, thereby obtaining a solid electrolyte material with excellent properties such as a wide electrochemical window, high ionic conductivity, high mechanical strength, good flame retardancy, and wide temperature applicability, which can be applied to high voltage systems above 4.6V.

[0007] To achieve the above objectives, in a first aspect, the present invention provides a deep eutectic-based in-situ polymerized solid electrolyte with high voltage resistance, wherein the in-situ polymerized solid electrolyte is obtained by in-situ polymerization of a precursor solution;

[0008] The precursor solution comprises: 30wt%-80wt% of a deep eutectic solution, 10wt%-50wt% of a polymerizable monomer, 1wt%-30wt% of an additive and 0.05wt%-10wt% of an initiator;

[0009] The deep eutectic solution comprises a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10; the hydrogen bond donor organic solvent comprises a nitrile solvent and a non-nitrile solvent in a molar ratio of 1:1-1:5, and the non-nitrile solvent comprises one or more of an amide solvent, a sulfonate solvent, a phosphate solvent, and a sulfone solvent;

[0010] The polymerizable monomers include monomers that can be polymerized by free radical initiation or monomers that can be polymerized by ring opening;

[0011] The additive comprises lithium nitrate and fluoroethylene carbonate in a mass ratio of 1:1-1:10;

[0012] The initiator includes a first initiator for initiating free radical polymerization or a second initiator for initiating ring-opening polymerization.

[0013] Preferably, the lithium salt includes one or more of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorooxalatoborate), lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate;

[0014] The nitrile solvent includes one or more of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, azelaic acid dinitrile, sebacononitrile, fumaronitrile, dimethylmalononitrile, p-fluorobenzonitrile, suberonitrile, and p-methylbenzonitrile;

[0015] The amide solvent includes one or more of acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, N,N-dimethylacetamide, and N,N-diallyl-2,2,2-trifluoroacetamide;

[0016] The sulfonate solvent includes: one or more of 1,3-propane sultone, propenyl-1,3-sultone, isopropyl methanesulfonate, 1,4-butane sultone, and (R,R)-1,2-bis(methylsulfonyloxymethyl)cyclohexane;

[0017] The phosphate ester solvent includes: one or more of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, trihexyl phosphate, and toluene diphenyl phosphate;

[0018] The sulfone solvent includes: one or more of dimethyl sulfone, dibutyl sulfone, ethyl methyl sulfone, diphenyl sulfone, 4,4'-difluorodiphenyl sulfone, 3-cyclobutene sulfone, and methyl phenyl sulfone.

[0019] More preferably, the nitrile solvent is suberonitrile; and the non-nitrile solvent is one or more of trimethyl phosphate, triethyl phosphate, dimethyl sulfone, 3-cyclobutene sulfone, N,N-dimethylacetamide, and acryl-1,3-sultone.

[0020] Preferably, the monomers for free radical-initiated polymerization include one or more of polyethylene oxide (PEO), polyethylene glycol diacrylate (PEGDA), polyethylene glycol methyl ether methacrylate (PMEA), butyl acrylate (BA), and butyl methacrylate (BMA); the first initiator includes azobisisobutyronitrile (AIBN);

[0021] The monomers for the ring-opening polymerization include: one or more of cyclic 1,3-dioxolane (DOL), ethylene carbonate (EC), vinyl ethylene carbonate (VEC), vinyl ethylene sulfite (VES), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and trioxymethylene (TXE); the second initiator includes: lithium difluorooxalatoborate (LiDFOB);

[0022] The polymerizable monomer is polymerized in situ by an initiator to form an organic framework in a deep eutectic-based in situ polymerized solid electrolyte that is resistant to high voltage.

[0023] In a second aspect, an embodiment of the present invention provides a method for preparing the high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte described in the first aspect, the preparation method comprising:

[0024] Mixing a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10, stirring until clear and transparent, to obtain a deep eutectic solution;

[0025] In accordance with the mass ratio, a polymerizable monomer, an additive, and an initiator are sequentially added to the deep eutectic solution, and the mixture is uniformly mixed to obtain a precursor solution; wherein the deep eutectic solution accounts for 30wt%-80wt%, the polymerizable monomer accounts for 10wt%-50wt%, the additive accounts for 1wt%-30wt% and the initiator accounts for 0.05wt%-10wt% in the precursor solution;

[0026] The precursor solution is initiated to obtain the deep eutectic-based in-situ polymerized solid electrolyte through a polymerization reaction.

[0027] Preferably, the preparation method is carried out in an inert atmosphere, and the water content and oxygen content of the inert atmosphere are both below 0.2 ppm.

[0028] Preferably, the initiation includes: one or more of thermal initiation, photoinitiation, photothermal composite initiation;

[0029] Wherein, the photothermal composite initiation includes thermal initiation combined with secondary initiation of ultraviolet light initiation, or ultraviolet light initiation combined with secondary initiation of thermal initiation;

[0030] The heat-induced heating temperature is 60-120° C., and the heat preservation time is 0.5 h-48 h.

[0031] Preferably, the deep eutectic solution comprises a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10; the hydrogen bond donor organic solvent comprises a nitrile solvent and a non-nitrile solvent in a molar ratio of 1:1-1:5, and the non-nitrile solvent comprises one or more of an amide solvent, a sulfonate solvent, a phosphate solvent, and a sulfone solvent;

[0032] The polymerizable monomers include monomers that can be polymerized by free radical initiation or monomers that can be polymerized by ring opening;

[0033] The additive comprises lithium nitrate and fluoroethylene carbonate in a mass ratio of 1:1-1:10;

[0034] The initiator includes a first initiator that initiates free radical polymerization or a second initiator that initiates ring-opening polymerization;

[0035] Wherein, the lithium salt includes: one or more of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorooxalatoborate), lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate;

[0036] The nitrile solvent includes one or more of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, azelaic acid dinitrile, sebacononitrile, fumaronitrile, dimethylmalononitrile, p-fluorobenzonitrile, suberonitrile, and p-methylbenzonitrile;

[0037] The amide solvent includes one or more of acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, N,N-dimethylacetamide, and N,N-diallyl-2,2,2-trifluoroacetamide;

[0038] The sulfonate solvent includes: one or more of 1,3-propane sultone, propenyl-1,3-sultone, isopropyl methanesulfonate, 1,4-butane sultone, and (R,R)-1,2-bis(methylsulfonyloxymethyl)cyclohexane;

[0039] The phosphate ester solvent includes: one or more of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, trihexyl phosphate, and toluene diphenyl phosphate;

[0040] The sulfone solvents include: one or more of dimethyl sulfone, dibutyl sulfone, ethyl methyl sulfone, diphenyl sulfone, 4,4'-difluorodiphenyl sulfone, 3-cyclobutene sulfone, and methyl phenyl sulfone;

[0041] The monomers for free radical-initiated polymerization include one or more of polyethylene oxide (PEO), polyethylene glycol diacrylate (PEGDA), polyethylene glycol methyl ether methacrylate (PMEA), butyl acrylate (BA), and butyl methacrylate (BMA); the first initiator includes azobisisobutyronitrile (AIBN);

[0042] The monomers for the ring-opening polymerization include: one or more of cyclic 1,3-dioxolane (DOL), ethylene carbonate (EC), vinyl ethylene carbonate (VEC), vinyl vinyl sulfite (VES), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and trioxymethylene (TXE); the second initiator includes: lithium difluorooxalatoborate (LiDFOB).

[0043] In a third aspect, an embodiment of the present invention provides an application of a high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte, wherein the deep eutectic solvent-based in-situ polymerized solid electrolyte is used as an electrolyte, a positive electrode coating material, a negative electrode coating material, or a diaphragm coating material for a secondary battery;

[0044] Among them, the high-voltage resistant deep eutectic-based in situ polymerized solid electrolyte is the high-voltage resistant deep eutectic-based in situ polymerized solid electrolyte described in the first aspect above, or the high-voltage resistant deep eutectic-based in situ polymerized solid electrolyte prepared by the preparation method described in the second aspect above.

[0045] In a fourth aspect, an embodiment of the present invention provides an energy storage device, the energy storage device comprising: a lithium battery, a battery cell or a battery pack;

[0046] The energy storage device includes the high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte described in the first aspect above, or includes the high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte prepared by the preparation method described in the second aspect above.

[0047] The high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte provided in an embodiment of the present invention is a high-voltage resistant in-situ polymerized solid electrolyte formed by in-situ compounding of an organic framework formed by in-situ polymerization of a deep eutectic solution, an additive, and a monomer, wherein there is a strong interaction between the two components of the hydrogen bond acceptor and the hydrogen bond donor of the deep eutectic solution, and the hydrogen bond donor is a composite system, in which the cyano group, combined with one or more of the strong polar groups such as phosphate groups, sulfonate groups, and amide groups, can exhibit significant antioxidant properties, thereby making the deep eutectic-based polymer electrolyte have a wide electrochemical window; at the same time, the synergistic effect of the unique composite additive can effectively stabilize the lithium metal negative electrode interface and avoid the negative effects caused by the presence of strong electron-withdrawing groups in the deep eutectic solution; the deep eutectic solution is introduced as a plasticizer and the in-situ polymerization of the monomer can reduce the crystallinity of the polymer, resolve a variety of lithium salts, and facilitate the transmission of lithium ions, thereby effectively improving the ionic conductivity. The deep eutectic solution, additives, organic framework formed by in-situ polymerization of monomers, etc. of the present invention work synergistically, and the obtained high-voltage resistant in-situ polymerized solid electrolyte has excellent properties such as wide electrochemical window, high ionic conductivity, high mechanical strength, good flame retardancy, and wide temperature applicability. It can be applied to high voltage systems above 4.6V, can effectively solve the solid-solid contact problem at the interface of solid-state batteries, and reduce the side reactions between the electrolyte and the lithium metal negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a differential scanning calorimetry curve of the deep eutectic-based in-situ polymerized solid electrolyte of Example 1 of the present invention;

[0049] Figure 2 The corresponding relationship curve between the ionic conductivity and temperature of the button-type battery in Example 1 of the present invention;

[0050] Figure 3 This is a Young's modulus distribution diagram of the in-situ polymerization of the precursor solution of Example 1 of the present invention;

[0051] Figure 4 The linear sweep voltammetric curves of the button cells of Example 1, Example 2 and Comparative Example 1 of the present invention;

[0052] Figure 5 This is a critical current density test curve of the Li|Li symmetric button cell constructed in Example 1 of the present invention;

[0053] Figure 6 This is a long cycle stability performance test curve of the Li|Li symmetric button battery constructed in Example 1 of the present invention;

[0054] Figure 7 Li|LiNi of Example 1 of the present invention 0.6 Co 0.2 Mn 0.2 O2 battery rate performance test curve at 30°C;

[0055] Figure 8 Li|LiNi of Example 1 of the present invention 0.6 Co 0.2 Mn 0.2 Long cycle stability test curve of O2 battery at 30°C;

[0056] Fig. 9 Li|LiNi of Example 1 of the present invention 0.9 Co 0.06 Mn 0.04 Leakage current test curve of O2 battery;

[0057] Fig.10 Li|LiNi of Example 1 of the present invention 0.9 Co 0.06 Mn 0.04 O2 battery rate performance test curve at 30°C;

[0058] Fig.11 Li|LiNi of Example 1 of the present invention 0.9 Co 0.06 Mn 0.04 Long cycle stability test curve of O2 battery at 30°C;

[0059] Fig.12 Li|LiNi of Example 3 of the present invention 0.9 Co 0.06 Mn 0.04 Long cycle stability test curve of O2 battery at 45°C;

[0060] Fig.13 Li|LiNi of Example 1 of the present invention 0.9 Co 0.06 Mn 0.04 O2 battery cyclic voltammetry curve;

[0061] Fig.14 Li|Li formed in Example 1 of the present invention 1.2 Ni 0.54 Co 0.12 Mn 0.12 Leakage current test curve of O2 battery;

[0062] Fig.15 Li|Li formed in Example 1 of the present invention1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 battery rate performance test curve at 30°C;

[0063] Fig.16 Li|Li of Example 7 of the present invention 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 battery rate performance test curve at 45°C;

[0064] Fig.17 Li|Li formed in Example 1 of the present invention 1.2 Ni 0.54 Co 0.12 Mn 0.12 Long cycle stability test curve of O2 battery at 30°C;

[0065] Fig.18 Li|Li of Example 7 of the present invention 1.2 Ni 0.54 Co 0.12 Mn 0.12 Long cycle stability test curve of O2 battery at 45°C. DETAILED DESCRIPTION

[0066] The embodiment of the present invention provides a high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte and the preparation and application thereof.

[0067] In the examples of the specific embodiments of the present invention, if there are specific experimental steps or conditions that are not described in detail, the conventional experimental operation steps and conditions recorded in the literature in the field can be followed; the reagents or instruments used without indicating the manufacturer are all conventional reagents and instruments that can be purchased commercially.

[0068] In order to facilitate a better understanding of the present invention, some technical terms are first explained below.

[0069] The technical term "deep eutectic solvents (DES)" refers to binary, ternary or multinary mixtures of compounds that are mainly bound by hydrogen bonds. These compounds are composed in a specific molar ratio to form a deep eutectic mixture. Due to intermolecular hydrogen bonds, the melting point of DES is lower than the melting point of each component, so that they remain liquid at room temperature. DES is also called an ionic liquid analog, room temperature molten salt. The DES of the present invention is formed by the interaction between a hydrogen bond acceptor (metal salt, such as LiTFSI, LiFSI, LiClO4, NaTFSI, NaFSI, NaPF6, etc.) and a hydrogen bond donor, including hydrogen bonds, Lewis acid-base interactions and van der Waals interactions. DES has the advantages of high ionic conductivity, low vapor pressure, good thermal stability, chemical stability and good non-flammability, and is low-cost and easy to prepare.

[0070] "In situ polymerization reaction" refers to the process of converting the liquid electrolyte inside the battery into a polymer solid electrolyte in situ through chemical or electrochemical methods.

[0071] "Hydrogen bond donor" refers to a molecule or group that is capable of forming hydrogen bonds through its hydrogen atoms with electronegative atoms (hydrogen bond acceptors) in other molecules.

[0072] "Hydrogen bond acceptors" refer to atoms with higher electronegativity (such as oxygen, nitrogen, fluorine, etc.) or molecules containing lone pairs of electrons. These atoms or groups can form stable hydrogen bonds with hydrogen bond donors by attracting hydrogen atoms.

[0073] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0074] The present invention proposes a high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte, which is obtained by in-situ polymerization of a precursor solution. The precursor solution comprises: 30wt%-80wt% of a deep eutectic solution, 10wt%-50wt% of a polymerizable monomer, 1wt%-30wt% of an additive, and 0.05wt%-10wt% of an initiator;

[0075] The deep eutectic solution includes a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10, which can be any ratio in the above range, such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc. The hydrogen bond donor organic solvent includes a nitrile solvent and a non-nitrile solvent in a molar ratio of 1:1-1:5, which can be any ratio in the above range, such as 1:1, 1:2, 1:3, 1:4, 1:5, etc. The non-nitrile solvent includes one or more of an amide solvent, a sulfonate solvent, a phosphate solvent, and a sulfone solvent. The polymerizable monomer includes a monomer for free radical initiated polymerization or a monomer for ring-opening polymerization; the additive includes lithium nitrate and fluoroethylene carbonate in a mass ratio of 1:1-1:10, which can be any ratio in the above range, such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, etc. The initiator includes a first initiator for initiating free radical polymerization or a second initiator for initiating ring-opening polymerization.

[0076] Specifically, in the deep eutectic solution:

[0077] The lithium salt is a hydrogen bond acceptor, and is bonded to the hydrogen bond donor through hydrogen bonds, including one or more of lithium bis(oxalatoborate), lithium bis(fluorosulfonylimide), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorooxalatoborate), lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate;

[0078] The nitrile solvents include one or more of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, azelaic acid dinitrile, sebacononitrile, fumaronitrile, dimethylmalononitrile, p-fluorobenzonitrile, suberonitrile, and p-methylbenzonitrile;

[0079] The amide solvents include: one or more of acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, N,N-dimethylacetamide, and N,N-diallyl-2,2,2-trifluoroacetamide;

[0080] Sulfonate solvents include: one or more of 1,3-propane sultone, propenyl-1,3-sultone, isopropyl methanesulfonate, 1,4-butane sultone, (R,R)-1,2-bis(methylsulfonyloxymethyl)cyclohexane;

[0081] The phosphate ester solvents include: one or more of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, trihexyl phosphate, and toluene diphenyl phosphate;

[0082] The sulfone solvents include: one or more of dimethyl sulfone, dibutyl sulfone, ethyl methyl sulfone, diphenyl sulfone, 4,4'-difluorodiphenyl sulfone, 3-cyclobutene sulfone, and methyl phenyl sulfone.

[0083] More preferably, it is a compound of suberonitrile and non-nitrile, the nitrile solvent is suberonitrile; the non-nitrile solvent is one or more of trimethyl phosphate, triethyl phosphate, dimethyl sulfone, 3-cyclobutene sulfone, N,N-dimethylacetamide, and acryl-1,3-sultone.

[0084] The deep eutectic solution used in the in-situ polymerized solid electrolyte of the present invention can be applied to different types of polymerizable monomers, not only to monomers that are easily polymerized by free radical-initiated polymerization, but also to monomers that are easily polymerized by ring-opening polymerization.

[0085] The monomers for free radical-initiated polymerization include one or more of polyethylene oxide (PEO), polyethylene glycol diacrylate (PEGDA), polyethylene glycol methyl ether methacrylate (PMEA), butyl acrylate (BA), and butyl methacrylate (BMA); the first initiator includes azobisisobutyronitrile (AIBN);

[0086] The monomers for ring-opening polymerization include: one or more of cyclic 1,3-dioxolane (DOL), ethylene carbonate (EC), vinyl ethylene carbonate (VEC), vinyl ethylene sulfite (VES), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and trioxymethylene (TXE); the second initiator includes: lithium difluorooxalatoborate (LiDFOB);

[0087] Among them, the polymerizable monomer is in situ polymerized by an initiator to form an organic framework in a deep eutectic-based in situ polymerized solid electrolyte that is resistant to high voltage.

[0088] In the present invention, by mixing the lithium salt and the hydrogen bond donor organic solvent in the above ratio, a strong interaction can be formed to obtain a deep eutectic mixture with high ionic conductivity, low vapor pressure, good thermal / chemical stability and good non-flammability.

[0089] Nitrile compounds have strong polarity and good antioxidant properties, which can effectively stabilize lithium salt anions and cations to prevent them from decomposing at high voltages. Non-nitrile hydrogen bond donors can form synergistic hydrogen bonds with nitriles to optimize the intermolecular interaction network. When nitriles and non-nitrile compounds are used in combination as hydrogen bond donors, they can exhibit significant antioxidant properties, inhibit the decomposition of electrolytes at high voltages, and form a stable deep eutectic network, further expanding the electrochemical window, so that deep eutectic-based polymer electrolytes exhibit a wide electrochemical window, which can be applied to high voltage systems above 4.6V or even above 4.8V.

[0090] In the preferred embodiment, the presence of two cyano groups in octanedinitrile improves the antioxidant property of the deep eutectic system, and the appropriate carbon chain length between the cyano groups balances the relationship between antioxidant property and viscosity and ion transport capacity, while the compounding of non-nitriles adjusts the viscosity of the deep eutectic solution. For example, the phosphorus-containing phosphate group in trimethyl phosphate has certain flame retardancy.

[0091] Therefore, the hydrogen bond donor organic solvent obtained by combining nitriles and non-nitriles in the above-mentioned proportion can not only exert the antioxidant property of the cyano group of the nitriles and broaden the electrochemical window of the polymer solid electrolyte, thereby adapting to high-voltage positive electrode systems such as high-nickel ternary and lithium-manganese-rich systems, but also improve its flame retardancy through specific phosphorus- and sulfur-containing groups in non-nitriles such as sulfonates and phosphates, thereby enhancing the thermal safety of the in-situ polymerized solid electrolyte.

[0092] Thus, a hydrogen bond network is formed between the lithium salt and the various strong polar groups in the hydrogen bond donor, which improves the degree of dissociation of lithium ions and makes the deep eutectic system have excellent properties such as antioxidant, flame retardant, and low saturated vapor pressure. The ratio between suberonitrile and non-nitrile is preferably 1:1-1:5, so that the synergistic performance of the two components can be fully exerted.

[0093] However, since the hydrogen bond donor organic solvent contained in the deep eutectic solution has a strong electron-withdrawing group, especially the hydrogen bond donor organic solvent of the two substances, the ability of the electron-withdrawing group is greatly enhanced, and the presence of the electron-withdrawing group easily leads to serious electron-loss chemical reaction (electron transfer) at the metal lithium negative electrode, triggering side reactions, destroying the metal lithium interface, and reducing its stability. Therefore, the present invention adopts a compound of fluoroethylene carbonate (FEC) and lithium nitrate (LiNO3) as an additive to synergistically improve the stability of the negative electrode interface of metal lithium.

[0094] Lithium nitrate has a very low lowest unoccupied molecular orbital (LUMO), which means it is more susceptible to reduction reactions on the surface of lithium metal anodes. The reduction product is Li3N, which can form a protective solid electrolyte interface (SEI) film on the surface of lithium metal to prevent further electron loss reactions. Under the synergistic effect of lithium nitrate, FEC can decompose to form LiF, a substance with very high chemical and electrochemical stability, which can further optimize the structure and properties of the SEI film. Therefore, the synergistic effect of Li3N and FEC is conducive to the formation of a solid electrolyte interface that is both chemically and electrochemically stable, avoiding side reactions between the strong polar groups of the hydrogen bond donor and the lithium metal anode, thereby effectively improving the long-cycle stability of the battery.

[0095] In summary, the high-voltage deep eutectic-based polymer solid electrolyte proposed in the present invention can be applied to high voltage systems above 4.6V or even above 4.8V, effectively solving the problem that traditional polymer electrolytes cannot match high voltage electrode material systems; it can effectively stabilize the lithium metal negative electrode interface and thus greatly improve the stability of the metal lithium negative electrode; the ionic conductivity can reach up to 10 -3 S / cm level, the ion conductivity is greatly improved; it has very excellent safety characteristics, especially when the hydrogen bond donor organic solvent of the deep eutectic solution is composited with nitrile and P- or N-containing phosphate and amide hydrogen bond donors, the obtained in-situ polymerized solid electrolyte has good flame retardant properties, thereby ensuring the safety of solid-state batteries.

[0096] The deep eutectic-based polymer solid electrolyte proposed in the present invention can be prepared by the following method. The entire preparation method is carried out in an inert atmosphere environment, and the water content and oxygen content of the inert atmosphere environment are both below 0.2ppm. The preparation steps include:

[0097] S1, mixing a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10, stirring until clear and transparent, to obtain a deep eutectic solution;

[0098] S2, adding polymerizable monomers, additives, and initiators to the deep eutectic solution in order according to the mass ratio, and mixing them evenly to obtain a precursor solution; wherein the deep eutectic solution accounts for 30wt%-80wt%, the polymerizable monomer accounts for 10wt%-50wt%, the additive accounts for 1wt%-30wt% and the initiator accounts for 0.05wt%-10wt% in the precursor solution;

[0099] S3, initiating the precursor solution to obtain the deep eutectic-based in-situ polymerized solid electrolyte through a polymerization reaction.

[0100] The initiation methods may include: one or more of thermal initiation, photoinitiation, and photothermal composite initiation; wherein, photothermal composite initiation includes thermal initiation combined with secondary initiation of ultraviolet light initiation, or ultraviolet initiation combined with secondary initiation of thermal initiation; the heating temperature of thermal initiation is 60-120°C, and the insulation time is 0.5h-48h.

[0101] In each of the above steps, the deep eutectic solution includes a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10; the hydrogen bond donor organic solvent includes a nitrile solvent and a non-nitrile solvent in a molar ratio of 1:1-1:5, and the non-nitrile solvent includes one or more of an amide solvent, a sulfonate solvent, a phosphate solvent, and a sulfone solvent; the polymerizable monomer includes a monomer for free radical initiated polymerization or a monomer for ring-opening polymerization; the additive includes lithium nitrate and fluoroethylene carbonate in a mass ratio of 1:1-1:10; the initiator includes a first initiator for initiating free radical polymerization or a second initiator for initiating ring-opening polymerization.

[0102] The lithium salt includes one or more of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorooxalatoborate), lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate;

[0103] The nitrile solvents include one or more of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, azelaic acid dinitrile, sebacononitrile, fumaronitrile, dimethylmalononitrile, p-fluorobenzonitrile, suberonitrile, and p-methylbenzonitrile;

[0104] The amide solvents include: one or more of acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, N,N-dimethylacetamide, and N,N-diallyl-2,2,2-trifluoroacetamide;

[0105] Sulfonate solvents include: one or more of 1,3-propane sultone, propenyl-1,3-sultone, isopropyl methanesulfonate, 1,4-butane sultone, (R,R)-1,2-bis(methylsulfonyloxymethyl)cyclohexane;

[0106] The phosphate ester solvents include: one or more of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, trihexyl phosphate, and toluene diphenyl phosphate;

[0107] Sulfone solvents include: one or more of dimethyl sulfone, dibutyl sulfone, ethyl methyl sulfone, diphenyl sulfone, 4,4'-difluorodiphenyl sulfone, 3-cyclobutene sulfone, and methyl phenyl sulfone;

[0108] The monomers for free radical-initiated polymerization include one or more of polyethylene oxide (PEO), polyethylene glycol diacrylate (PEGDA), polyethylene glycol methyl ether methacrylate (PMEA), butyl acrylate (BA), and butyl methacrylate (BMA); the first initiator includes azobisisobutyronitrile (AIBN);

[0109] The monomers for ring-opening polymerization include: one or more of cyclic 1,3-dioxolane (DOL), ethylene carbonate (EC), vinyl ethylene carbonate (VEC), vinyl vinyl sulfite (VES), fluoroethylene carbonate (FEC), vinylene carbonate (VC), and trioxymethylene (TXE); the second initiator includes: lithium difluorooxalatoborate (LiDFOB).

[0110] The present invention forms a high-voltage resistant in-situ polymerized solid electrolyte by in-situ compounding of an organic framework formed by in-situ polymerization of a deep eutectic solution, an additive and a monomer. The in-situ polymerization reaction of the precursor solution in the battery system can change the point contact between the polymer electrolyte and the positive electrode to surface contact, thereby effectively solving the solid-solid contact problem at the interface of the solid-state battery, greatly reducing the interface impedance, and thus improving the battery performance.

[0111] The present invention introduces a deep eutectic solution as a plasticizer into an organic framework formed by in-situ polymerization of monomers, uses lithium salt hydrogen bonds as acceptors, and makes a strong interaction between the two components of the hydrogen bond acceptor and the hydrogen bond donor by compounding the hydrogen bond acceptor and the specific hydrogen bond donor. The hydrogen bond donor contains a cyano group, which is compounded with strong polar groups such as phosphate groups, sulfonate groups, and amide groups. The compound group can show significant antioxidant properties, so that the deep eutectic-based polymer electrolyte has a wide electrochemical window, which solves the problem that traditional polymer electrolytes such as polyethylene oxide (PEO) cannot match high-voltage electrode material systems. The deep eutectic-based in-situ polymerization solid electrolyte prepared by the present invention can be applied to high-voltage systems above 4.6V or even above 4.8V. When it is matched with a lithium-rich positive electrode material, it can also effectively suppress the gas production problem of the lithium-rich positive electrode material and the dissolution problem of transition metal ions, thereby achieving the cycle stability of a 4.6V lithium-rich manganese-based positive electrode material and greatly improving the energy density of solid-state lithium batteries.

[0112] The presence of strong electron-withdrawing groups in the hydrogen-bond donor organic solvent in the deep eutectic solution can significantly improve the material's antioxidant properties, but it can also lead to high reactivity with lithium metal and the formation of undesirable interface byproducts. The present invention utilizes a unique composite additive synergistic effect to effectively stabilize the lithium metal negative electrode interface, avoiding side reactions between hydrogen-bond donors such as nitriles, sulfones, and phosphates and the lithium metal negative electrode. Through the synergistic effect between the additives fluoroethylene carbonate (FEC) and lithium nitrate (LiNO3), on the one hand, lithium nitrate, which is difficult to dissolve in traditional carbonate electrolytes, is used in the deep eutectic solution additive. Lithium nitrate has the lowest lowest unoccupied molecular orbital (LUMO). When forming SEI, lithium nitrate can be preferentially reduced to form Li3N on the lithium metal negative electrode. On the other hand, it can promote fluoroethylene carbonate to generate LiF, which is conducive to the formation of a solid electrolyte interface that takes into account both chemical and electrochemical stability, avoiding side reactions between the strong polar groups of the hydrogen-bond donor and the lithium metal negative electrode, thereby effectively improving the long-cycle stability of the deep eutectic-based polymer electrolyte.

[0113] The present invention introduces a deep eutectic solution as a plasticizer into the organic framework formed by in-situ polymerization of monomers. Compared with inorganic particles, the deep eutectic electrolyte can be evenly dispersed in the precursor solution, thereby effectively reducing the crystallinity of the polymer and facilitating the polymer chain segment to transport lithium ions. In addition, the polar functional groups of the deep eutectic solution have a strong interaction with lithium ions, so a variety of lithium salts can be dissociated, ensuring rapid ion transport, thereby increasing the ionic conductivity to 10 -4 ~10 -3 S / cm order of magnitude.

[0114] The deep eutectic solution formed by the present invention based on hydrogen bonds, intermolecular Lewis acid-base and electrostatic interactions has low vapor pressure and high flash point, and exhibits significant safety. In particular, the in-situ polymerized solid electrolyte obtained by compounding nitriles with P-containing, N-containing phosphate esters and amide-containing hydrogen bond donors has good flame retardant properties.

[0115] The high-voltage resistant deep eutectic solvent-based in-situ polymerized solid electrolyte obtained by the present invention can be used as electrolyte, positive electrode coating material, negative electrode coating material or diaphragm coating material of secondary batteries, and can be applied to lithium batteries, battery cells, battery packs, lithium battery groups or lithium battery modules. It can be widely used in consumer electronics, electric vehicles, large-scale energy storage and other fields, and also has good application prospects in large-scale energy storage systems.

[0116] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0117] Example 1

[0118] This embodiment provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0119] The organic solvent suberonitrile and trimethyl phosphate are mixed uniformly in a molar ratio of 1:2 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:6, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0120] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0121] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0122] Example 2

[0123] This embodiment provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0124] The organic solvent suberonitrile and trimethyl phosphate are mixed uniformly in a molar ratio of 1:1 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:6, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0125] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0126] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0127] Example 3

[0128] This embodiment provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0129] The organic solvent suberonitrile and dimethyl sulfone are mixed uniformly in a molar ratio of 1:2 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:6, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0130] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol methyl ether acrylate PMEA, 0.1g of fluoroethylene carbonate (FEC), 20mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0131] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0132] Example 4

[0133] This embodiment provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0134] The organic solvent suberonitrile and N,N-dimethylacetamide are mixed uniformly at a molar ratio of 1:1 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed at a molar ratio of 1:4, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0135] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol methyl ether acrylate PMEA, 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0136] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0137] Example 5

[0138] This embodiment provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0139] The organic solvent suberonitrile and propenyl-1,3-sultone are uniformly mixed in a molar ratio of 1:2 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:6, and the mixture is magnetically stirred at a speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0140] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 50mg of fluoroethylene carbonate (FEC), 50mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0141] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0142] Example 6

[0143] This embodiment provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0144] The organic solvent suberonitrile and triethyl phosphate are mixed uniformly in a molar ratio of 1:2 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:6, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0145] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0146] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0147] Example 7

[0148] This embodiment provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0149] The organic solvent suberonitrile and 3-cyclobutene sulfone are mixed uniformly in a molar ratio of 1:1 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:4, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0150] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 20mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0151] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0152] Comparative Example 1

[0153] This comparative example provides a method for preparing a composite solid electrolyte of a common carbonate electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0154] Weigh 0.287 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), dissolve it in 1 mL of ethylene carbonate (EC), mix and stir magnetically at a speed of 600 rpm for 4 h to obtain a colorless and transparent carbonate electrolyte;

[0155] Take 0.7g of the above carbonate electrolyte, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring, continue stirring, the stirring speed is 600rpm, the time is 10min, and a uniformly mixed electrolyte precursor solution is obtained;

[0156] The precursor solution was heated at 60° C. for 24 hours to obtain the in-situ polymerized solid electrolyte of Comparative Example 1.

[0157] Comparative Example 2

[0158] This comparative example provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0159] The organic solvent suberonitrile and trimethyl phosphate are mixed uniformly at a molar ratio of 1:20 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed at a molar ratio of 1:6, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0160] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0161] The precursor solution was heated at 60° C. for 24 hours to obtain the deep eutectic solvent-based in-situ polymerized solid electrolyte of Comparative Example 2.

[0162] Comparative Example 3

[0163] This comparative example provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0164] The organic solvent suberonitrile and trimethyl phosphate are mixed uniformly in a molar ratio of 1:2 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:6, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0165] Take 0.8 g of the deep eutectic solution, slowly add 0.2 g of polyethylene glycol diacrylate (PEGDA) and 1 mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring, continue stirring at a speed of 600 rpm for 10 min to obtain a uniformly mixed electrolyte precursor solution;

[0166] The precursor solution was heated at 60° C. for 24 hours to obtain the deep eutectic solvent-based in-situ polymerized solid electrolyte of Comparative Example 3.

[0167] Comparative Example 4

[0168] This comparative example provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0169] The organic solvent suberonitrile and trimethyl phosphate are mixed uniformly in a molar ratio of 1:2 to obtain a hydrogen bond donor organic solvent, and then lithium bistrifluoromethylsulfonyl imide (LiTFSI) and the hydrogen bond donor organic solvent are weighed in a molar ratio of 1:6, and the mixture is magnetically stirred at a stirring speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0170] Take 0.2g of deep eutectic solution, slowly add 0.7g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0171] The precursor solution was heated at 60° C. for 24 hours to obtain the deep eutectic solvent-based in-situ polymerized solid electrolyte of Comparative Example 4.

[0172] Comparative Example 5

[0173] This comparative example provides a method for preparing a composite solid electrolyte of a deep eutectic electrolyte and a polymer, wherein the preparation method is carried out in an argon protective atmosphere and an environment system in which the water content and the oxygen content are both below 0.2 ppm, and comprises the following steps:

[0174] Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and hydrogen bond donor suberonitrile were weighed in a molar ratio of 1:6, mixed and magnetically stirred at a speed of 600 rpm for 4 hours to obtain a colorless transparent solution, which is a deep eutectic solution;

[0175] Take 0.7g of deep eutectic solution, slowly add 0.2g of polyethylene glycol diacrylate (PEGDA), 0.1g of fluoroethylene carbonate (FEC), 10mg of lithium nitrate (LiNO3), and 1mg of thermal polymerization initiator azobisisobutyronitrile (AIBN) under stirring conditions, continue stirring at a stirring speed of 600rpm for 10min to obtain a uniformly mixed electrolyte precursor solution;

[0176] The precursor solution was heated at 60°C for 24 hours to obtain a deep eutectic solvent-based in-situ polymerized solid electrolyte.

[0177] The above embodiments and comparative examples were tested:

[0178] 1. Physical and chemical index testing.

[0179] (1) Differential scanning calorimetry test:

[0180] Differential scanning calorimetry (DSC) was tested using a Netzsch DSC 214 Polyma instrument with a scan rate of 5 K / min, a starting temperature of 20°C, and an end temperature of 350°C. A high-pressure crucible was used to prevent mass loss. 8.86 mg of the post-polymerization deep eutectic-based in-situ polymerized solid electrolyte of Example 1 was taken. The test results are shown in FIG. Figure 1 .

[0181] pass Figure 1 It can be seen that the starting temperature of the first exothermic peak of the deep eutectic-based in-situ polymerized solid electrolyte of Example 1 is 196.3°C, and the peak temperature is 216.4°C, which indicates that the safety performance of the in-situ polymerized solid electrolyte of the present invention is greatly improved, and no decomposition of any form will occur before 190°C.

[0182] (2) Ionic conductivity test of in-situ composite solid electrolyte:

[0183] First, SS|GEL|SS battery was assembled using CR2032 button battery shell, where SS was a stainless steel gasket and GEL was a deep eutectic-based in-situ polymerized solid electrolyte of the present invention. The preparation method was as follows: a glass fiber separator GF was placed between the positive and negative electrodes, and 100 μL of the electrolyte precursor solution of Example 1 was dripped onto it. After the SS|GEL|SS battery was assembled, it was placed in a 60°C oven for in-situ polymerization for 24 h.

[0184] Then, the assembled button cell was tested for high and low temperature ionic conductivity: the polymerized button cell was placed in a high and low temperature oven, and the target temperature was set and then left to stand for 3 hours until the temperature stabilized. The target temperature settings were as follows: 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C.

[0185] The impedance of the button cell was tested at the above target temperature. Specifically, the SS|GEL|SS battery was tested by using a Zahner electrochemical workstation. The test frequency range was 1MHz-0.1Hz, the AC voltage amplitude was 10mV, the test temperature was 10℃ to 80℃, and the step length was 10℃, that is, the test temperature increased by 10℃ each time. The ionic conductivity test results are shown in Figure 2 And as shown in Table 1.

[0186]

[0187] Table 1

[0188] like Figure 2 As shown in Table 1, the ionic conductivity of the deep eutectic-based in-situ polymerized solid electrolyte of Example 1 is basically linearly related to the test temperature. The ionic conductivities at 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, and 80°C are 0.254×10 -3 S / cm, 0.403×10 -3 S / cm, 0.591×10 -3 S / cm, 0.815×10 -3 S / cm, 1.076×10 -3 S / cm, 1.372×10 -3 S / cm, 1.686×10 -3 S / cm, 2.017×10 -3 S / cm. It can be seen that the solid electrolyte obtained in Example 1 of the present invention has high ionic conductivity at both low and high temperatures, reaching 10 -4 S / cm, and the ionic conductivity is as high as 10 above 50°C -3 S / cm, the deep eutectic-based in-situ polymerized solid electrolyte of the present invention can ensure the effective transmission of ions.

[0189] (3) Atomic force microscope test Young's modulus:

[0190] 100 μL of the electrolyte precursor solution of Example 1 was dripped onto the glass fiber diaphragm, and the sample was heated at 60°C for in-situ polymerization for 24 h in a glove box environment with an argon protective atmosphere and a water content and an oxygen content of less than 0.2 ppm. The sample was scanned by an atomic force microscope (AFM, Bruker Dimension Icon) in Peak Force QNM mode with a scanning range of 5 μm×5 μm. The Young's modulus test results are shown in FIG. Figure 3 shown.

[0191] The distribution of Young's modulus of the sample of Application Example 1 after in-situ polymerization is as follows: Figure 3 As shown, after analysis, the average Young's modulus is 108 MPa, and the deep eutectic-based in-situ polymerized solid electrolyte exhibits good mechanical strength.

[0192] 2. Button half-cell electrochemical performance test.

[0193] The electrochemical performance of the lithium batteries prepared in the above embodiments and comparative examples was tested, and the test results were analyzed and discussed. The systems of the embodiments and comparative examples were assembled into button batteries to test the electrochemical performance of the lithium batteries. The button batteries were assembled as follows:

[0194] (1) Assembly of Li|SS button cell: Li|GEL|SS battery was assembled using CR2032 button cell shell. The lithium sheet specification was Φ16*0.5mm, SS was a stainless steel gasket, and the diaphragm was a glass fiber diaphragm. During the assembly process, 100uL of the electrolyte precursor solution of each embodiment and comparative example was added dropwise, and the assembled battery was placed in an oven at 60°C for in-situ polymerization for 24h.

[0195] (2) Assembly of Li|Li symmetrical button cell: Li|GEL|Li battery was assembled using CR2032 button cell shell. The lithium sheet had a specification of Φ12.5*0.5 mm, and the separator was a glass fiber separator. During the assembly process, 100uL of the electrolyte precursor solution of each embodiment and comparative example was added dropwise, and the assembled battery was placed in an oven at 60°C for in-situ polymerization for 24h.

[0196] (3)Li|GEL|LiNi 0.6 Co 0.2 Mn 0.2 Assembly of O2 button cell: LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622) cathode was purchased from Xiamen Tungsten New Energy Materials Co., Ltd. 0.6 Co 0.2 Mn 0.2O2 (NCM622), Super P and PVDF were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to prepare a slurry with a solid content of about 30%, which was then coated on the surface of aluminum foil. 0.6 Co 0.2 Mn 0.2 The surface loading of O2 is 2.0 mg / cm 2 , and vacuum dried at 80°C for 12 hours to obtain the positive electrode sheet, which was then cut.

[0197] In an argon atmosphere glove box, the above LiNi 0.6 Co 0.2 Mn 0.2 O2 positive electrode sheet as positive electrode, lithium sheet (0.5mm thick) as negative electrode, glass fiber separator, assembled Li|GEL|LiNi 0.6 Co 0.2 Mn 0.2 CR2032 button battery with O2 structure. During the assembly process, 100 μL of the electrolyte precursor solution of each embodiment and comparative example was added dropwise, and the assembled battery was placed in an oven at 60° C. for in-situ polymerization for 24 hours.

[0198] (4)Li|GEL|LiNi 0.9 Co 0.06 Mn 0.04 Assembly of O2 button cell: LiNi 0.9 Co 0.06 Mn 0.04 O2 (Ni90) cathode material comes from Xiamen Tungsten New Energy Materials Co., Ltd. 0.9 Co 0.06 Mn 0.04 O2(Ni90), Super P and PVDF were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to prepare a slurry with a solid content of about 30%, which was then coated on the surface of aluminum foil. 0.9 Co 0.06 Mn 0.04 The O2 surface loading is about 2.0 mg / cm 2 , and vacuum dried at 80°C for 12 hours to obtain the positive electrode sheet, which was then cut.

[0199] In an argon atmosphere glove box, the above LiNi 0.9 Co 0.06 Mn 0.04 O2 positive electrode sheet as positive electrode, lithium sheet (0.5mm thick) as negative electrode, glass fiber separator, assembled Li|GEL|LiNi 0.9 Co 0.06 Mn 0.04During the assembly process of the CR2032 button battery with O2 structure, 100 μL of the electrolyte precursor solution of each embodiment and comparative example was added dropwise, and the assembled battery was placed in an oven at 60° C. for in-situ polymerization for 24 hours.

[0200] (5)Li|GEL|Li 1.2 Ni 0.54 Co 0.12 Mn 0.12 Assembly of Li O2 coin cells 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 (LRM) cathode material comes from Ningbo Fuli Battery Material Technology Co., Ltd. 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2(LRM), SuperP and PVDF were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to prepare a slurry with a solid content of about 30%, which was then coated on the surface of aluminum foil. 1.2 Ni 0.54 Co 0.12 Mn 0.12 The surface loading of O2 is about 2.0 mg / cm 2 , and vacuum dried at 120°C for 12 hours to obtain a positive electrode sheet, which was then cut.

[0201] In an argon atmosphere glove box, the above Li 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 positive electrode sheet as positive electrode, lithium sheet (0.5mm thick) as negative electrode, glass fiber separator, assembled Li|GEL|Li 1.2 Ni 0.54 Co 0.12 Mn 0.12 During the assembly process of the CR2032 button battery with O2 structure, 100 μL of the electrolyte precursor solution of each embodiment and comparative example was added dropwise, and the assembled battery was placed in an oven at 60° C. for in-situ polymerization for 24 hours.

[0202] The electrochemical performance of the prepared battery was tested, and the steps and specific test parameters were as follows:

[0203] 1) Electrochemical stability window test: The in-situ polymerized solid electrolyte obtained in Example 1, Example 2 and Comparative Example 1 was subjected to linear sweep voltammetry (LSV) test using an Autolab electrochemical workstation. The test temperature was room temperature 25°C. The LSV scan range was between open circuit voltage (OCV) and 6V (vs. Li+ / Li), and the scan rate was 0.1mV / s. The results are shown in Figure 2. Figure 4 .

[0204] Figure 4 It is shown that in the linear sweep voltammetric curve, the electrochemical windows of Example 1 and Example 2 are 5.9 V and 5.3 V respectively, which are much higher than the electrochemical window of 4.5 V of Comparative Example 1. This indicates that compared with the existing solid-state polymerization monomers, the combination of deep eutectic solution and polymerizable monomers enhances the antioxidant properties of the polymer solid electrolyte and broadens the electrochemical window.

[0205] 2) Critical current density test at 30°C: The Li|Li symmetrical button cell obtained by in-situ polymerization of solid electrolyte in Example 1 was tested using a blue electric tester. The button cell was placed in a high-temperature oven at 30°C for a current incremental charge and discharge test. The current density increased from 0.05 mA / cm 2 Starting from 0.05mA / cm2 per charge and discharge cycle 2 The charging and discharging time is 1 hour each week. Figure 5 .from Figure 5 It is shown that the maximum critical current density of Example 1 is 0.45 mA / cm 2 , with very high stability to lithium.

[0206] 3) Long cycle stability test of Li|Li symmetric button cell at 30°C: The Li|Li symmetric button cell obtained by in-situ polymerization of solid electrolyte in Example 1 was tested using a blue electric tester. The polymerized button cell was placed in a high temperature oven at 30°C for constant current charge and discharge test with a current density of 0.1 mA / cm 2 Starting from this time, the charging and discharging time is 1 hour each week. The results are as follows Figure 6 .

[0207] from Figure 6 It is shown in the figure that the Li|Li symmetric button cell using the electrolyte of Example 1 has a long-term stable cycle of more than 1000 h, and the polarization voltage is only about 30 mV, indicating that the deep eutectic-based in-situ polymerized solid electrolyte has a stable interface with the lithium negative electrode.

[0208] 4) Li|LiNi at 30℃ 0.6 Co 0.2 Mn 0.2O2 battery rate charge and discharge performance test: The Li|LiNi obtained by in-situ polymerization of solid electrolytes in Examples 1, 2, 6 and Comparative Examples 1, 2, 4 was tested using a blue electric tester. 0.6 Co 0.2 Mn 0.2 The O2 button battery was tested with a voltage range of 2.5V-4.3V. The constant current charge and discharge cycles were performed at 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C for 5 weeks, and then at 0.1C and 0.5C for 5 weeks. The test results are shown in Table 2 and Figure 7 shown.

[0209]

[0210] Table 2

[0211] As shown in Table 2 and Figure 7 As shown, the in-situ polymerized solid electrolyte of Example 1 obtains a solid-state battery with a discharge specific capacity of 181.3 mAh / g, 168.8 mAh / g, 153.2 mAh / g, 133.6 mAh / g, 101.3 mAh / g and 66.8 mAh / g after 5 weeks of charge and discharge cycles at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C and 3 C, respectively, and the coulombic efficiency after 5 weeks of cycles is 97.42%, 98.78%, 99.38%, 99.65%, 99.88% and 99.94%, respectively. The in-situ polymerized solid electrolyte of Example 2 obtains a solid-state battery with a discharge specific capacity of 178.8 mAh / g, 172.3 mAh / g, 158.9 mAh / g, 149.8 mAh / g, 124.8 mAh / g and 106.6 mAh / g after 5 weeks of charge and discharge cycles at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C and 3 C, respectively. The in-situ polymerized solid electrolyte of Comparative Example 1 obtains a solid-state battery with a discharge specific capacity of 178.8 mAh / g, 172.3 mAh / g, 158.9 mAh / g, 149.8 mAh / g, 124.8 mAh / g and 106.6 mAh / g after 5 weeks of charge and discharge cycles at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C and 3 C, respectively. The amounts are 176.6mAh / g, 164.3mAh / g, 144.5mAh / g, 126.3mAh / g, 103.2mAh / g and 83.1mAh / g respectively. It can be seen from the rate performance of Examples 1, 2 and Comparative Example 1 that, compared with the in-situ solidification electrolysis using commonly used carbonates, the deep eutectic-based in-situ polymerized solid electrolyte of the present invention has higher specific capacity at 0.1C, 0.2C, 0.5C and 1C, and Example 2 has higher specific capacity at 2C and 3C, and has better rate performance.

[0212] The molar ratios of the organic solvent suberonitrile to trimethyl phosphate in Examples 1 and 2 are 1:2 and 1:1, respectively, while the molar ratio of suberonitrile to trimethyl phosphate in Comparative Example 2 is 1:20. It can be seen that the molar ratio of suberonitrile to trimethyl phosphate in Comparative Example 2 is significantly higher than that in Examples 1 and 2. The in-situ polymerized solid electrolyte of Comparative Example 2 obtains a solid-state battery with a discharge specific capacity of 173.3 mAh / g, 160.8 mAh / g, 141.3 mAh / g, 122.4 mAh / g, 89.9 mAh / g and 57.1 mAh / g after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.5C, 1C, 2C and 3C, respectively. It can be seen from the rate performance of Examples 1, 2 and Comparative Example 2 that when the molar ratio of suberonitrile to trimethyl phosphate is not within the range defined by the present invention, its specific capacity at each rate will be significantly reduced. Compared with Example 1, the specific capacity of Comparative Example 2 at 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C is reduced by 8 mAh / g, 8 mAh / g, 11.9 mAh / g, 11.2 mAh / g, 11.4 mAh / g, and 9.7 mAh / g, respectively. Compared with Example 2, the specific capacity of Comparative Example 2 at 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C is reduced by 5.5 mAh / g, 11.5 mAh / g, 17.6 mAh / g, 27.4 mAh / g, 34.9 mAh / g, and 49.5 mAh / g, respectively. Therefore, it can be seen that the molar ratio of suberonitrile to trimethyl phosphate is within the scope of the present invention, especially when the ratio of the two is 1:1, it has a better rate performance.

[0213] The molar ratio of the organic solvent suberonitrile to trimethyl phosphate in Example 1 and Comparative Example 4 is the same as 1:2, while the mass percentage of the deep eutectic solution in Example 1 is 69.2%, while the mass percentage of the deep eutectic solution in Comparative Example 4 is 19.8%. The in-situ polymerized solid electrolyte of Comparative Example 4 obtains a solid-state battery with a discharge specific capacity of 160.2 mAh / g, 144.3 mAh / g, 101.7 mAh / g, 63.3 mAh / g, 8.7 mAh / g and 6.1 mAh / g after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.5C, 1C, 2C and 3C, respectively. It can be seen from the rate performance of Example 1 and Comparative Example 4 that when the mass ratio of the deep eutectic solution is not within the scope of the present invention, its specific capacity at each rate is greatly reduced. Compared with Example 1, the specific capacities of Comparative Example 4 at 0.1C, 0.2C, 0.5C, 1C, 2C, and 3C are reduced by 21.1 mAh / g, 24.5 mAh / g, 51.5 mAh / g, 70.3 mAh / g, 92.6 mAh / g, and 60.7 mAh / g, respectively. Therefore, it can be seen that when the content of the deep eutectic solution is within the ratio range of the present invention, it has excellent rate performance.

[0214] 5) Li|LiNi at 30℃ 0.6 Co 0.2 Mn 0.2 O2 battery long cycle stability performance test: The Li|LiNi obtained by in-situ polymerization of solid electrolyte in Example 1, Example 2, Example 6 and Comparative Example 1, Comparative Example 3, Comparative Example 5 was tested using a blue electric tester. 0.6 Co 0.2 Mn 0.2 O2 button batteries were tested with a voltage range of 2.5V-4.3V. They were first charged and discharged at a constant current of 0.1C for 3 weeks, and then charged and discharged at a current of 0.5C for 200 cycles. The results are shown in Table 3 and Figure 8 shown.

[0215]

[0216] Table 3

[0217] In-situ polymerized solid electrolyte and positive electrode LiNi of Examples 1, 2, and 6 of the present invention 0.6 Co 0.2 Mn 0.2 O2 matching obtains that the discharge specific capacity of the solid-state battery after 200 cycles of charge and discharge at 0.5C is 114.33mAh / g, 159.73mAh / g and 125.41mAh / g respectively. It can be seen that in Example 2, when the molar ratio of suberonitrile to trimethyl phosphate is 1:1, it has the highest cycle stability.

[0218] In-situ polymerized solid electrolytes and positive electrode LiNi 0.6 Co 0.2 Mn 0.2 O2 matching obtains that the discharge specific capacity of the solid-state battery after 200 cycles of charge and discharge at 0.5C is 98.67mAh / g, 41.60mAh / g and 94.59mAh / g respectively. Comparative Example 1 is a conventional in-situ polymerized solid electrolyte system, Comparative Example 3 does not contain the composite additive of fluoroethylene carbonate and lithium nitrate in Example 1, and the hydrogen bond donor organic solvent in Comparative Example 5 is a single solvent, suberonitrile.

[0219] Compared with comparative example 1, the discharge specific capacity of example 1 after 200 charge and discharge cycles is 15.66 mAh / g higher. Therefore, compared with conventional polycarbonate, the deep eutectic-based in-situ polymerization solid electrolyte system of the present invention has better cycle stability.

[0220] Compared with comparative example 3, the specific capacity of embodiment 1 after 200 cycles of charge and discharge is 72.73 mAh / g higher. It can be seen that the composite additive of fluoroethylene carbonate (FEC) and lithium nitrate (LiNO3) with a mass ratio of 10:1 can significantly improve the cycle stability of the present invention.

[0221] Compared with comparative example 5, the specific capacity of embodiment 1 after 200 charge-discharge cycles is 19.74 mAh / g higher. It can be seen that the present invention can significantly improve the cycle stability by using a composite hydrogen bond donor organic solvent.

[0222] It can be seen from the long cycle tests of Example 1 and Comparative Example 5 that the present invention uses a deep eutectic solution and adopts a composite additive, which has better long cycle stability.

[0223] 6) Li|LiNi at 30℃ 0.9 Co 0.06 Mn 0.04 Leakage current test of O2 battery: The Li|LiNi obtained by in-situ polymerization of solid electrolyte in Example 1 was tested using a blue electric tester. 0.9 Co 0.06 Mn 0.04 The O2 button battery was tested by first charging it at a constant current of 0.1C to 4.3V, and then charging it at a constant voltage to 4.3V, 4.4V, 4.5V, 4.6V, 4.7V, 4.8V, and 4.9V for 10h each. The results are as follows: Fig. 9 .

[0224] like Fig. 9 As shown, for high nickel ternary LiNi 0.9 Co 0.06 Mn 0.04 For the O2 positive electrode system, the battery of Example 1 was used until it was charged to 4.8 V, and the leakage current was still lower than 10 μA, which indicates the antioxidant property of the deep eutectic-based in-situ polymerized solid electrolyte.

[0225] 7) Li|LiNi at 30℃ 0.9 Co 0.06 Mn 0.04 O2 battery rate charge and discharge performance test: The Li|LiNi obtained by in-situ polymerization of solid electrolytes in Example 1, Example 4, Example 5 and Comparative Example 1 and Comparative Example 2 was tested using a blue electric tester. 0.9 Co 0.06 Mn 0.04 The O2 button battery was tested with a voltage range of 2.8V-4.25V. The constant current charge and discharge cycles were performed at 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, and 1C for 5 weeks, and then at 0.1C for 5 weeks. The results are shown in Table 4 and Fig.10shown.

[0226]

[0227]

[0228] Table 4

[0229] As shown in Table 4 and Fig.10 As shown, the hydrogen bonding organic donor solvent in Example 1 is suberonitrile and trimethyl phosphate in a molar ratio of 1:2, the hydrogen bonding organic donor solvent in Example 4 is suberonitrile and N,N-dimethylacetamide in a molar ratio of 1:1, and the hydrogen bonding organic donor solvent in Example 5 is suberonitrile and propenyl-1,3-sultone in a molar ratio of 1:2.

[0230] The solid-state battery obtained by the in-situ polymerization solid electrolyte of Example 1 has a discharge capacity of 229.9 mAh / g, 225.6 mAh / g, 217.3 mAh / g, 202.3 mAh / g, 192.9 mAh / g, 138.6 mAh / g and 226.7 mAh / g after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, 1C and 0.1C, respectively. The coulombic efficiency after 5 weeks of circulation is 99.40%, 99.51%, 99.43%, 99.65%, 100.10%, 100.40% and 99.76%, respectively. The in-situ polymerized solid electrolyte of Example 4 obtains a solid-state battery with a discharge capacity of 225.4 mAh / g, 223.5 mAh / g, 221.6 mAh / g, 208.7 mAh / g, 199.3 mAh / g, 141.6 mAh / g and 222.7 mAh / g after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, 1C and 0.1C, respectively. The in-situ polymerized solid electrolyte of Example 5 obtains a solid-state battery with a discharge capacity of 228.1 mAh / g, 219.8 mAh / g, 214.3 mAh / g, 208.6 mAh / g, 191.1 mAh / g, 133.3 mAh / g and 224.5 mAh / g after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, 1C and 0.1C, respectively. It can be seen that the in-situ polymerized solid electrolyte obtained by combining suberonitrile with different non-nitrile organic solvents is very similar to the positive electrode LiNi 0.9 Co 0.06 Mn 0.04 The in-situ polymerized solid electrolytes obtained by matching O2 have very good rate performance.

[0231] The solid-state battery obtained by the in-situ polymerization solid electrolyte of Comparative Example 1 has a discharge capacity of 221.3mAh / g, 193.4mAh / g, 188.7mAh / g, 176.1mAh / g, 113.4mAh / g, 84.1mAh / g and 199.9mAh / g after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, 1C and 0.1C, respectively. The coulomb efficiency after 5 weeks of circulation is 97.36%, 98.51%, 98.68%, 99.11%, 99.23%, 99.89% and 98.13%, respectively. The solid-state battery obtained by the in-situ polymerization solid electrolyte of Comparative Example 2 has a discharge specific capacity of 217.5 mAh / g, 202.3 mAh / g, 194.2 mAh / g, 180.1 mAh / g, 141.3 mAh / g, 96.6 mAh / g and 209.8 mAh / g after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.3C, 0.4C, 0.5C, 1C and 0.1C, respectively.

[0232] Through Examples 1, 4, 5 and Comparative Examples 1 and 2, respectively, high nickel positive electrode LiNi 0.9 Co 0.06 Mn 0.04 It can be seen from the rate performance when O2 is matched that the deep eutectic-based in-situ polymerized solid-state electrolyte of the present invention has very excellent rate performance when adapted to the 9-series high nickel (Ni90) positive electrode material.

[0233] 8) Li|LiNi at 30℃ 0.9 Co 0.06 Mn 0.04 O2 battery long cycle stability performance test: The Li|LiNi obtained by in-situ polymerization of solid electrolytes in Example 1, Example 4, Example 5 and Comparative Example 1 and Comparative Example 2 was tested using a blue electric tester. 0.9 Co 0.06 Mn 0.04 O2 button batteries were tested with a voltage range of 2.8V-4.25V. They were first charged and discharged at a constant current of 0.1C for 3 weeks, and then charged at a current of 0.2C and discharged at a current of 0.5C for 60 cycles. The test results are shown in Table 5 and Fig.11 shown.

[0234]

[0235] Table 5

[0236] In-situ polymerized solid electrolyte and positive electrode LiNi of Examples 1, 4 and 5 of the present invention 0.9 Co 0.06 Mn 0.04O2 matching obtains that the discharge specific capacity of the solid-state battery after 60 cycles of charge and discharge at 0.5C is 204.59mAh / g, 186.01mAh / g and 195.23mAh / g respectively. It can be seen that the polymeric solid electrolyte obtained by compounding suberonitrile and trimethyl phosphate in Example 1 matches the high-nickel positive electrode and has higher cycle stability.

[0237] In-situ polymerized solid electrolytes of Comparative Examples 1 and 2 and LiNi 0.9 Co 0.06 Mn 0.04 O2 matching obtains that the discharge specific capacity of the solid-state battery after 60 cycles of charge and discharge at 0.5C is 93.15mAh / g and 100.06mAh / g respectively. Comparative Example 1 is a conventional in-situ polymerized solid electrolyte system, and in Comparative Example 2, suberonitrile and trimethyl phosphate are in a molar ratio of 1:20.

[0238] Compared with Comparative Example 1, the discharge specific capacity of Example 1 after 60 charge and discharge cycles is higher than that of Example 1 by 111.44 mAh / g. Therefore, compared with conventional polycarbonates, the deep eutectic-based in-situ polymerized solid electrolyte system of the present invention has significantly improved cycle stability when matched with a high-nickel positive electrode.

[0239] Compared with comparative example 2, the specific capacity of embodiment 1 after 60 cycles of charge and discharge is 104.53 mAh / g higher. It can be seen that the solid electrolyte obtained by reasonably controlling the ratio of nitrile and non-nitrile in the hydrogen bond donor organic solvent of the present invention has better cycle stability when matched with a high nickel positive electrode.

[0240] Through the long cycle test of the solid-state battery with in-situ polymerized solid electrolyte and high nickel positive electrode of the embodiment and comparative example, it can be seen that the deep eutectic solution of the present invention combined with the same polymerizable monomer has higher long cycle stability.

[0241] 9) Li|LiNi at 45℃ 0.9 Co 0.06 Mn 0.04 O2 battery long cycle stability performance test: The Li|LiNi obtained by in-situ polymerization of solid electrolytes in Example 3 and Comparative Example 1 was tested using a blue electric tester. 0.9 Co 0.06 Mn 0.04 O2 button battery was tested. The voltage range was 2.8V-4.25V. It was first charged and discharged at a constant current of 0.1C for 3 weeks, then charged at a current of 0.2C, and then discharged at a current of 0.5C for 60 cycles. The test results are shown in Table 6 and Fig.12 shown.

[0242] Example 3 Comparative Example 1 0.1C first week discharge capacity mAh / g 231.64 227.45 0.1C first week coulomb efficiency 91.45% 87.39% 0.5C first week discharge capacity mAh / g 219.28 211.31 0.5C first week coulomb efficiency 93.02% 89.27% Discharge capacity mAh / g after 60 cycles 188.02 113.27 Capacity retention rate 85.82% 53.60%

[0243] Table 6

[0244] It can be seen from the long cycle tests of Example 3 and Comparative Example 1 that, compared with the use of common carbonate electrolytes at high temperatures, the use of deep eutectic solutions in combination with the same polymerizable monomer has higher long cycle stability.

[0245] 10) Li|LiNi at 30℃ 0.9 Co 0.06 Mn 0.04 O2 battery cyclic voltammetry test: The Li|LiNi obtained by in-situ polymerization of solid electrolyte in Example 1 was tested using the Autolab electrochemical workstation. 0.9 Co 0.06 Mn 0.04 The O2 button cell was subjected to cyclic voltammetry test with a voltage range of 2.8V-4.3V and a voltage sweep rate of 0.1mV / s. The results are as follows Fig.13 .

[0246] like Fig.13 As shown, the oxidation peaks of the battery using Example 1 in the first three weeks were 3.87V, 3.85V, and 3.84V, respectively, the reduction peaks in the first week were 4.03V, 3.93V, and 3.69V, respectively, and the reduction peaks in the second week were 4.03V, 3.95V, and 3.69V, respectively, and then stabilized in the following weeks. This shows that Example 1 exhibits good electrochemical stability in the process of forming the in-situ interface layer, indicating that a stable and protective interface layer has been formed.

[0247] 11) Li|Li at 30℃ 1.2 Ni 0.54 Co 0.12 Mn 0.12 Leakage current test of O2 battery: The Li|Li obtained by in-situ polymerization of solid electrolyte in Example 1 was tested using a blue electric tester. 1.2 Ni 0.54 Co 0.12 Mn 0.12 The O2 button battery was tested by first charging it at a constant current of 0.1C to 4.3V, and then charging it at a constant voltage to 4.3V, 4.4V, 4.5V, 4.6V, 4.7V, 4.8V, and 4.9V for 10h each. The results are as follows: Fig.14 .

[0248] like Fig.14 As shown, for lithium-rich manganese-based Li 1.2 Ni 0.54 Co 0.12 Mn 0.12For the O2 positive electrode system, although the leakage current initially exceeds 10 μA when the battery of Example 1 is charged to 4.5 V, which is related to the participation of oxygen atoms in the lithium-rich manganese-based material in redox, as the charging voltage gradually increases until it is charged to 4.9 V, the leakage current is less than 10 μA, which indicates the antioxidant property of the deep eutectic-based in-situ polymerized solid electrolyte.

[0249] 12) Li|Li at 30℃ 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 battery rate charge and discharge performance test: The Li|Li obtained by in-situ polymerization of solid electrolytes in Example 1 and Comparative Example 1 was tested using a blue electric tester. 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 button battery was tested. The voltage range was 2V-4.6V, and the constant current charge and discharge cycle was performed for 5 weeks at 0.1C, 0.2C, 0.3C, 0.5C, 1C, 2C, and 3C respectively, and then the charge and discharge cycle was performed for 5 weeks at 0.1C. The results are shown in Table 7 and Fig.15 shown.

[0250]

[0251]

[0252] Table 7

[0253] Example 1 Test data are shown in Table 7 and Fig.15 As shown, the solid-state battery obtained by applying the deep eutectic-based in-situ polymerized solid electrolyte of Example 1 has a discharge specific capacity of 250.7mAh / g, 227.5mAh / g, 213.8mAh / g, 188.2mAh / g, 128.1mAh / g, 47.9mAh / g, and 30.4mAh / g respectively after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.3C, 0.5C, 1C, 2C, and 3C. After 5 weeks of cycling, the coulomb efficiency is 98.03%, 98.59%, 98.76%, 99.36%, 100.45%, 95.76%, 102.29%, and 96.93% respectively. However, the in-situ polymerized electrolyte of Comparative Example 1 is not resistant to oxidation and cannot generate a stable interface, resulting in continuous side reactions, resulting in overcharging in the first week and the battery cannot operate normally.

[0254] 13) Li|Li at 45℃ 1.2 Ni 0.54 Co 0.12 Mn 0.12O2 battery rate charge and discharge performance test: The Li|Li obtained by in-situ polymerization of solid electrolytes in Example 7 and Comparative Example 1 was tested using a blue electric tester. 1.2 Ni 0.54 Co 0.12 Mn 0.12 The O2 button battery was tested with a voltage range of 2V-4.6V. The constant current charging and discharging was performed at 0.1C, 0.2C, 0.3C, 0.5C, 1C, 2C, and 3C, and then at 0.1C. The results are shown in Table 8 and Fig.16 shown.

[0255] Different charge and discharge current conditions Example 7 Discharge capacity mAh / g 0.1C 293.9 0.2C 272.6 0.3C 258.3 0.5C 235.5 1C 176.4 2C 73.7 3C 36.9 0.1C 251.9

[0256] Table 8

[0257] Example 7 Test data are shown in Table 8 and Fig.16 As shown, the solid-state battery obtained by applying the deep eutectic-based in-situ polymerized solid electrolyte of Example 7 at high temperature has a discharge capacity of 293.9mAh / g, 272.6mAh / g, 258.3mAh / g, 235.5mAh / g, 176.4mAh / g, 73.7mAh / g, 36.9mAh / g and 251.9mAh / g respectively after 5 weeks of charge and discharge cycles at 0.1C, 0.2C, 0.3C, 0.5C, 1C, 2C, 3C and 0.1C. After 5 weeks of cycling, the coulomb efficiency is 96.51%, 96.96%, 97.30%, 98.13%, 98.27%, 99.36%, 98.71% and 93.83% respectively. However, the in-situ polymerized electrolyte of Comparative Example 1 is not resistant to oxidation and cannot generate a stable interface, resulting in continuous side reactions, resulting in overcharging in the first week and the battery cannot operate normally.

[0258] 14) Li|Li at 30℃ 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 battery long cycle stability performance test: The Li|Li obtained by in-situ polymerization of solid electrolytes in Example 1 and Comparative Example 1 was tested using a blue electric tester. 1.2 Ni 0.54 Co 0.12 Mn 0.12 The O2 button battery was tested with a voltage range of 2V-4.6V. It was first charged and discharged at a constant current of 0.1C to 4.4V and 4.5V for 1 week each for low voltage pre-formation, and then charged and discharged at a constant current of 0.1C at a cut-off voltage of 4.6V for 3 weeks, and then charged and discharged at a current of 0.2C for 60 weeks. The results of Example 1 are shown in Table 9 and Fig.17 shown.

[0259] Example 1 0.1C first week discharge capacity mAh / g 247.99 0.1C first week coulomb efficiency 96.69% 0.2C first week discharge capacity mAh / g 232.21 0.2C first week coulomb efficiency 95.28% Discharge capacity mAh / g after 60 cycles 203.00 Capacity retention rate 87.42%

[0260] Table 9

[0261] In-situ polymerized solid electrolyte of Example 1 matches the lithium-rich positive electrode Li 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2, 0.2C current charging cycle after 60 weeks of discharge specific capacity of 203.00mAh / g, capacity retention rate of 87.42%, with a high capacity retention rate. 1.2 Ni 0.54 Co 0.12 Mn 0.12 Because O2 is not resistant to oxidation, it cannot form a stable interface, which leads to continuous side reactions, resulting in overcharging in the first week and the battery cannot operate normally.

[0262] It can be seen from the long cycle tests of Example 1 and Comparative Example 1 that, when compounded with the same polymerizable monomer, the deep eutectic solution of the present invention can have higher long cycle stability.

[0263] 15) Li|Li at 45℃ 1.2 Ni 0.54 Co 0.12 Mn 0.12 O2 battery long cycle stability performance test: The Li|Li of Example 7 and Comparative Example 1 were tested using a blue electricity tester. 1.2 Ni 0.54 Co 0.12 Mn 0.12 The O2 button battery was tested with a voltage range of 2V-4.6V. It was first charged and discharged at a constant current of 0.1C to 4.4V and 4.5V for 1 week each for low voltage pre-formation, and then charged and discharged at a constant current of 0.1C at a cut-off voltage of 4.6V for 3 weeks to form, and then charged at a current of 0.2C. The results of Example 7 are shown in Table 10 and Fig.18 shown.

[0264] Example 7 0.1C first week discharge capacity mAh / g 270.44 0.1C first week coulomb efficiency 95.19% 0.2C first week discharge capacity mAh / g 257.70 0.2C first week coulomb efficiency 95.76% Discharge capacity after 50 cycles mAh / g 145.19 Capacity retention rate 56.34%

[0265] Table 10

[0266] In-situ polymerized solid electrolyte of Example 7 matches the lithium-rich positive electrode Li 1.2 Ni 0.54 Co 0.12 Mn 0.12The discharge capacity after 50 cycles of O2, 0.2C current charging is 145.19 mAh / g. However, the in-situ polymerized electrolyte of Comparative Example 1 is not resistant to oxidation at a high temperature of 45°C and cannot form a stable interface, resulting in continuous side reactions, resulting in overcharging in the first week and the battery cannot operate normally.

[0267] It can be seen from the long cycle tests of Example 7 and Comparative Example 1 that the deep eutectic-based in-situ polymerized solid electrolyte of the present invention generates a stable electrode-electrolyte interface at high temperature and exhibits good long cycle stability.

[0268] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high voltage resistant deep eutectic based in-situ polymerized solid electrolyte, characterized in that: The in-situ polymerized solid electrolyte is obtained by an in-situ polymerization reaction of a precursor solution; The precursor solution comprises: 30wt%-80wt% of a deep eutectic solution, 10wt%-50wt% of a polymerizable monomer, 1wt%-30wt% of an additive and 0.05wt%-10wt% of an initiator; The deep eutectic solution comprises a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10; the hydrogen bond donor organic solvent comprises a nitrile solvent and a non-nitrile solvent in a molar ratio of 1:1-1:5, and the non-nitrile solvent comprises one or more of an amide solvent, a sulfonate solvent, a phosphate solvent, and a sulfone solvent; The polymerizable monomers include monomers that can be polymerized by free radical initiation or monomers that can be polymerized by ring opening; The additive comprises lithium nitrate and fluoroethylene carbonate in a mass ratio of 1:1-1:10; The initiator includes a first initiator for initiating free radical polymerization or a second initiator for initiating ring-opening polymerization.

2. The high voltage resistant deep eutectic-based in-situ polymerized solid electrolyte according to claim 1, characterized in that: The lithium salt includes one or more of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorooxalatoborate), lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate; The nitrile solvent includes one or more of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, azelaic acid dinitrile, sebacononitrile, fumaronitrile, dimethylmalononitrile, p-fluorobenzonitrile, suberonitrile, and p-methylbenzonitrile; The amide solvent includes one or more of acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, N,N-dimethylacetamide, and N,N-diallyl-2,2,2-trifluoroacetamide; The sulfonate solvent includes: one or more of 1,3-propane sultone, propenyl-1,3-sultone, isopropyl methanesulfonate, 1,4-butane sultone, and (R,R)-1,2-bis(methylsulfonyloxymethyl)cyclohexane; The phosphate ester solvent includes: one or more of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, trihexyl phosphate, and toluene diphenyl phosphate; The sulfone solvent includes: one or more of dimethyl sulfone, dibutyl sulfone, ethyl methyl sulfone, diphenyl sulfone, 4,4'-difluorodiphenyl sulfone, 3-cyclobutene sulfone, and methyl phenyl sulfone.

3. The high voltage resistant deep eutectic-based in-situ polymerized solid electrolyte according to claim 2, characterized in that: The nitrile solvent is suberonitrile; the non-nitrile solvent is one or more of trimethyl phosphate, triethyl phosphate, dimethyl sulfone, 3-cyclobutene sulfone, N,N-dimethylacetamide, and propenyl-1,3-sultone.

4. The high voltage resistant deep eutectic-based in-situ polymerized solid electrolyte according to claim 1, characterized in that: The monomers for free radical polymerization include: one or more of polyethylene oxide PEO, polyethylene glycol diacrylate PEGDA, polyethylene glycol methyl ether methacrylate PMEA, butyl acrylate BA, butyl methacrylate BMA; the first initiator includes: azobisisobutyronitrile AIBN; The monomers for the ring-opening polymerization include: one or more of cyclic 1,3-dioxolane DOL, vinyl carbonate EC, vinyl ethylene carbonate VEC, vinyl sulfite VES, fluoroethylene carbonate FEC, vinylene carbonate VC, and trioxymethylene TXE; the second initiator includes: lithium difluorooxalatoborate LiDFOB; The polymerizable monomer is polymerized in situ by an initiator to form an organic framework in a deep eutectic-based in situ polymerized solid electrolyte that is resistant to high voltage.

5. A method for preparing a high voltage resistant deep eutectic-based in-situ polymerized solid electrolyte according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Mixing a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10, stirring until clear and transparent, to obtain a deep eutectic solution; In accordance with the mass ratio, a polymerizable monomer, an additive, and an initiator are sequentially added to the deep eutectic solution, and the mixture is uniformly mixed to obtain a precursor solution; wherein the deep eutectic solution accounts for 30wt%-80wt%, the polymerizable monomer accounts for 10wt%-50wt%, the additive accounts for 1wt%-30wt% and the initiator accounts for 0.05wt%-10wt% in the precursor solution; The precursor solution is initiated to obtain the deep eutectic-based in-situ polymerized solid electrolyte through a polymerization reaction.

6. The preparation method according to claim 5, characterized in that: The preparation method is carried out in an inert atmosphere environment, and the water content and oxygen content of the inert atmosphere environment are both below 0.2 ppm.

7. The preparation method according to claim 5, characterized in that: The initiation includes: one or more of thermal initiation, photoinitiation, photothermal composite initiation; Wherein, the photothermal composite initiation includes thermal initiation combined with secondary initiation of ultraviolet light initiation, or ultraviolet light initiation combined with secondary initiation of thermal initiation; The heat-induced heating temperature is 60-120° C., and the heat preservation time is 0.5 h-48 h.

8. The preparation method according to claim 5, characterized in that: The deep eutectic solution comprises a lithium salt and a hydrogen bond donor organic solvent in a molar ratio of 1:1-1:10; the hydrogen bond donor organic solvent comprises a nitrile solvent and a non-nitrile solvent in a molar ratio of 1:1-1:5, and the non-nitrile solvent comprises one or more of an amide solvent, a sulfonate solvent, a phosphate solvent, and a sulfone solvent; The polymerizable monomers include monomers that can be polymerized by free radical initiation or monomers that can be polymerized by ring opening; The additive comprises lithium nitrate and fluoroethylene carbonate in a mass ratio of 1:1-1:10; The initiator includes a first initiator that initiates free radical polymerization or a second initiator that initiates ring-opening polymerization; Wherein, the lithium salt includes: one or more of lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorooxalatoborate), lithium difluorophosphate, lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroarsenate, and lithium perchlorate; The nitrile solvent includes one or more of malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, azelaic acid dinitrile, sebacononitrile, fumaronitrile, dimethylmalononitrile, p-fluorobenzonitrile, suberonitrile, and p-methylbenzonitrile; The amide solvent includes one or more of acetamide, N-methylacetamide, trifluoroacetamide, N-methyltrifluoroacetamide, N,N-dimethylacetamide, and N,N-diallyl-2,2,2-trifluoroacetamide; The sulfonate solvent includes: one or more of 1,3-propane sultone, propenyl-1,3-sultone, isopropyl methanesulfonate, 1,4-butane sultone, and (R,R)-1,2-bis(methylsulfonyloxymethyl)cyclohexane; The phosphate ester solvent includes: one or more of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, trihexyl phosphate, and toluene diphenyl phosphate; The sulfone solvent includes one or more of dimethyl sulfone, dibutyl sulfone, ethyl methyl sulfone, diphenyl sulfone, 4,4'-difluorodiphenyl sulfone, 3-cyclobutene sulfone, and methyl phenyl sulfone; The monomers for free radical polymerization include: one or more of polyethylene oxide PEO, polyethylene glycol diacrylate PEGDA, polyethylene glycol methyl ether methacrylate PMEA, butyl acrylate BA, butyl methacrylate BMA; the first initiator includes: azobisisobutyronitrile AI BN; The monomers for the ring-opening polymerization include: one or more of cyclic 1,3-dioxolane DOL, vinyl carbonate EC, vinyl ethylene carbonate VEC, vinyl vinyl sulfite VES, fluoroethylene carbonate FEC, vinylene carbonate VC, and trioxymethylene TXE; the second initiator includes: lithium difluorooxalatoborate Li DFOB.

9. Application of a high voltage resistant deep eutectic-based in-situ polymerized solid electrolyte, characterized in that: The deep eutectic solvent-based in-situ polymerized solid electrolyte is used as an electrolyte, a positive electrode coating material, a negative electrode coating material or a diaphragm coating material for a secondary battery; Among them, the high-voltage resistant deep eutectic-based in situ polymerized solid electrolyte is the high-voltage resistant deep eutectic-based in situ polymerized solid electrolyte described in any one of claims 1 to 4 above, or the high-voltage resistant deep eutectic-based in situ polymerized solid electrolyte prepared by the preparation method described in any one of claims 5 to 8 above.

10. An energy storage device, characterized in that: The energy storage device includes: a lithium battery, a battery cell or a battery pack; The energy storage device comprises the high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte described in any one of claims 1-4 above, or comprises the high-voltage resistant deep eutectic-based in-situ polymerized solid electrolyte prepared by the preparation method described in any one of claims 5-8 above.

Citation Information

Cited By

  • Preparation method and application of polymer electrolyte

    CN121260911A

  • Safe electrolyte, preparation method thereof and lithium battery

    CN121484213A

  • Ultrahigh-energy-density solid-state lithium metal battery and preparation method thereof

    CN121618064A

  • Preparation method and application of high-temperature-resistant and high-pressure-resistant solid electrolyte membrane with gradient structure

    CN121662938A

  • Local high-concentration in-situ polymerization gel electrolyte and application thereof in lithium metal battery

    CN122025779A